Th.o.m.a.s.: new insights into theory of mind in adolescents with autism spectrum disorder - Fadda, Roberta; Congiu, Sara; Doneddu, Giuseppe; Carta, Marinella; Piras, Francesco; Gabbatore, Ilaria; Bosco, Francesca M. (Frontiers in Psychology, 2024)
Previous studies indicated atypical Theory of Mind (ToM) abilities in individuals with Autism Spectrum Disorder (ASD) at different ages. However, research focused on adolescents with ASD is still rare. This study aims to fill the gaps in the literature, by investigating ToM abilities in adolescents with ASD and in a group of typically developing ones. We applied the Theory of Mind Assessment Scale (Th.o.m.a.s.), a semi-structured interview that allows a multi-dimensional measurement of ToM, including different perspectives (first/second-order, first/third-person, egocentric/allocentric), various mental states (emotions, desires, beliefs) and metacognitive abilities related with mental states (awareness, relation, and strategies). The results indicated that ToM develops atypically in ASD, with strengths and weaknesses. First, participants with ASD were comparable to controls in some specific ToM aspects, i.e., third-person ToM, both from an egocentric and an allocentric perspective. However, they were significantly weaker in attributing an understanding of the mental states of others, both in first-and second-order ToM scenarios. Second, they showed the same level of awareness about mental states as controls, but they were significantly weaker in conceptualizing the relationship between mental states and behavior. Also, they found it very difficult to think about possible strategies that they or others might employ to realize desires and needs. Finally, they performed similarly to controls in understanding emotions, while they poorly understood desires and beliefs. These results point out the distinctive characteristics of ToM development in individuals with ASD, with important implications for individualized interventions. These results point out the clinical utility of the Th.o.m.a.s. as a sensitive tool to measure individual differences, which might be very useful in defining effective individualized interventions to improve Theory of Mind abilities in adolescents with ASD.